Reoperation after surgical treatment for benign prostatic hyperplasia: a systematic review - He, Weixiang; Ding, Ting; Niu, Zhiping; Hao, Chunlin; Li, Chengbin; Xu, Zhicheng; Jing, Yuming; Qin, Weijun (Frontiers in Endocrinology, 2023)
Context: Surgical treatment is important for male lower urinary tract symptoms (LUTS) management while review regarding the risks of reoperation is few. Objective: To systematically evaluate the current evidence regarding reoperation rates of surgical treatment for LUTS recommended by guidelines. Evidence Acquisition: Eligible studies published up to July 2023, were searched from Databases (PubMed, Embase, and Web of Science). The STATA was applied to process meta-analysis. Random effects models were used to calculate pooled incidences of reoperation and 95% confidence intervals (CIs). Evidence Synthesis: A total of 119 studies with 130106 patients were included. The re-operation rate of TURP was 4.0%, 5.0%, 6.0% and 7.7% (1, 2, 3 and 5 yr, respectively, below procedures also applied). The re-operation rate of PKRP was 3.5%, 3.6%, 5.7% and 6.6%. The re-operation rate of HoLEP was 2.4%, 3.3%, 5.4% and 6.6%. The re-operation rate of PVP was 3.3%, 4.1%, 6.7% and 7.1%. The re-operation rate of AquaBeam was 2.6%, 3.1%, 3.0% and 4.1%. The re-operation rate of PAE was 12.2%, 20.0%, 26.4% and 23.8%. The re-operation rate of TUMT was 9.9%, 19.9%, 23.3% and 31.2%. The re-operation rate of TUIP was 13.4% (5 yr). The re-operation rate of OP was 1.3% and 4.4% (1 and 5 yr, respectively). The re-operation rate of ThuLEP was 3.7%, 7.7% and 8.4% (1, 2 and 5 yr, respectively). Conclusions: Our results summarized the re-operation rates of ten surgical procedures over a follow-up duration of 1, 2, 3 and 5 years, which could provide reference for urologists and LUTS patients.